Circulación de noticias e ideas ultramontanas en el Río de la Plata tras la instalación de la primera nunciatura en la América ibérica (1830-1842) - Ignacio Martínez (Historia Crítica, 2014)
This article analyzes the epistolary circuit that linked the first nunciature of Spanish America—set up in 1830 in Rio de Janeiro—with the defenders of the Pope's authority in Argentina. The study seeks to understand up to what point the ecclesiastical government's patronage logic changed after the Independence, how the Pope was present in the churches of Rio de la Plata, and how this presence was mediated by the activities of local Ultramontane ecclesiastics. To achieve this goal, the author uses the collected letters found in the Archive of the Nunciature of Rio de Janeiro, conserved in the Archivio Segreto Vaticano (Italy). Using this information it is possible to reconstruct the channels through which news and ideas circulated between ultramontane groups.